Capacidade de mascaramento de sistemas restauradores de resina composta pela técnica de estratificação - Miotti, Leonardo Lamberti (2015)
Tooth discoloration is considered a challenging clinical condition for restoration procedures. Layering technique with resin composites of different translucencies can be applied to cover-up discolored substratum and produce esthetic harmonic restorations. The aim of the present study was to assess the masking ability of the layering technique with the following resin composites restoration systems - IPS Empress Direct (Ivoclar Vivadent), Charisma Diamond (Heraeus Kulzer) and Filtek Z350XT (3M-ESPE). Ninety specimens with 1.5mm thick were produced and divided in groups according to the restoration system and resin composite combination. Color measurements were carried out by reflectance spectrophotometer (SP60 - EX-Rite) through CIE L*a*b* color system against a C4 shade background (C4), and an inherent color background (IC). These two backgrounds simulate a severely discolored substratum (C4) and a tooth surface with no discoloration (IC). The total color difference (ΔE) between both color measures indicates the masking ability of the resin combination. The normal data distribution was verified with Kolmogorov-Smirnov test. The mean ΔE* values were analyzed by ANOVA and Tukey s post hoc tests (α =0.05). Three groups presented ΔE* values under clinical acceptance threshold (ΔE*≦3,3): 1.5mm Dentin; 1.0mm Dentin / 0.5mm Body and 1.0mm Dentin / 0.5mm Enamel, all groups from Z350 XT restoration system. Filtek Z350 XT system was capable to mask C4 background. The dentin shade of this system was considered more effective when compared to IPS Empress and Charisma Diamond dentin shade resins and masked the discolored background in single layer mode or combined with Z350 enamel and body shade through layering technique.